Kajian Sosiologis terhadap Tradisi Haji dalam Komunitas Muslim Sekarbela Kota Mataram - Yuhanna; Huda, Miftahul (Kartika: Jurnal Studi Keislaman, 2025)
This study provides an in-depth exploration of the Hajj-related traditions that have developed within the community of Sekarbela, Mataram, as a reflection of the synergy between spiritual and social dimensions of communal life. In the Sekarbela community, a variety of meaningful pre-departure traditions are preserved and practiced, including ziarah kubur (visiting ancestral graves) as an act of reverence, selakaran (communal prayer gatherings) for blessings and collective supplication, and nyimpen (entrusting valuable items or messages to pilgrims) as part of the spiritual and social preparation for the pilgrimage. Using a qualitative descriptive approach, this study captures both the forms of these traditions and their social and economic impacts. The findings reveal that these practices not only reinforce social ties and maintain interpersonal connections, but also cultivate a strong sense of solidarity, communal belonging, and ukhuwah islamiyah (Islamic brotherhood). The Hajj thus becomes a sacred and emotionally resonant occasion that deepens familial and communal bonds. However, the study also identifies challenges, particularly social pressures faced by prospective pilgrims from economically disadvantaged backgrounds due to prevailing expectations to observe these traditions in full. Nonetheless, the traditions remain flexible and adaptive, allowing individuals to participate according to their means without undue economic burden. Overall, the Hajj traditions in Sekarbela represent a living heritage that harmoniously integrates religious devotion, social unity, and local cultural wisdom